A methodological approach to assess the hazard of underground cavities subjected to environmental weathering. (December 2018) - Castellanza, Riccardo; Lollino, Piernicola; Ciantia, Matteo
Graphical abstract: Abstract: Soft highly porous carbonate rocks, such as calcarenites, and soluble sulphate rocks, such as gypsum, are very common in the Mediterranean region and, due to their microstructure and chemical composition, are prone to water induced weathering mechanisms. Cliffs, underground cavities and other morphological features in such formations are hence affected by intense erosion phenomena and weathering processes responsible for unexpected collapses and sinkholes. Just considering the Apulian region (Italy), 150 sinkholes have been recorded since 1925, with increasing frequency since 2000 (Fiore et al., 2018 ). The geosystem's failure is often the short- or long-term result of a very complex hydro-chemo-mechanical process taking place at the micro-scale which can be detected and analysed by means of field and laboratory experimental test campaigns. Therefore, stability problems are often related to changes of the mechanical properties of the rock forming the cave caused by environmental weathering processes, despite the external boundary conditions are not changing with time. The paper deals with the assessment of hazard associated with the stability of abandoned underground caves, which is nowadays frequently required for land and urban planning activities. A methodological approach for hazard assessment based on a step-by-step procedure is proposed. This includes in-situ surveys, laboratory experimental studies, theoretical analyses and finally numerical investigations. The approach derives from the experience developed from several case studies analysed by the authors. In this work, two of these are presented. The first one concerns the stability of an anthropic cavity in a calcarenite formation which is affected by a water induced short-term and long-term debonding processes. The second one regards the stability of a three-level abandoned gypsum mine, the lowest level being partially flooded by water. The methodological procedure aims to evaluate the factors controlling the change of the mechanical properties of the rock so that efficient remediation measures can be designed in order to avoid any further decay of the rock mass stability with time. The proposed methodological approach, validated on real case studies, shows the convenience of performing advanced experimental, theoretical and numerical studies to properly assess the hazard in space and time and to better design the mitigation measures if they are required. The adoption of the proposed approach reduced the remediation costs of the second case study of one order of magnitude.